Harta sebagai Amanah dalam Islam: Analisis Konsep Kepemilikan dan Pemanfaatannya Berdasarkan QS. Al-Baqarah Ayat 254, 261, dan 267 - Dini Zaskia Hafid Sinaga; Dinda Safitri Saragih; Elpianti Sahara Pakpahan (Medan Resource Center, 2026)
Property (māl) in Islam is regarded as a trust from Allah SWT that must be acquired, managed, and utilized in accordance with Sharia principles. This study aims to analyze the Islamic concept of wealth and property ownership through the interpretation of Surah Al-Baqarah verses 254, 261, and 267, supported by relevant hadiths. This research employs a library research approach by examining the Qur’an, hadiths, classical and contemporary scholarly works, and related academic literature. The findings reveal that Islam acknowledges individual property ownership while emphasizing that such ownership is fiduciary rather than absolute, since ultimate ownership belongs to Allah SWT. The analysis demonstrates that the selected verses establish an integrated framework of Islamic wealth management encompassing responsible ownership, ethical acquisition, quality spending, and philanthropy as essential components of socioeconomic justice. The study contributes to the development of Islamic economics by reinforcing the Qur’anic foundation of wealth governance and highlighting the integration of spiritual accountability with social responsibility in property management. In conclusion, wealth in Islam functions not only as an economic asset but also as a means of worship and the realization of public welfare (maslahah).